STRATEGIC TRANSFORMATION OF POWER UTILITIES IN THE ERA OF ENERGY TRANSITION: A SYSTEMATIC LITERATURE REVIEW AND FUTURE RESEARCH AGENDA - Rio Afrianda (EBID: Ekonomi Bisnis Digital, 2026)
This study systematically reviews the strategic transformation of power utilities in the context of the global energy transition, driven by decarbonization, digitalization, and decentralization. Using a PRISMA-based approach, this research analyzes peer-reviewed articles indexed in Scopus and Web of Science from 2000 to 2025. The findings reveal four dominant research clusters: (1) external drivers, (2) strategic responses, (3) transformation capabilities, and (4) performance outcomes. Despite the rapid growth of the literature, existing studies remain fragmented, with limited integration between strategic management theories and energy transition research. This study contributes by proposing a novel integrative framework—SET-UP (Strategic Energy Transformation of Utilities under Pressure)—which explains how external pressures shape strategic responses and organizational capabilities, ultimately influencing performance outcomes. The paper advances the literature by bridging strategic management and energy transition studies and outlines a future research agenda focusing on emerging economies, capability development, and longitudinal analysis.